Evaluation of Wheat and Orange-fleshed Sweet Potato Composite Flour Fortified with African Yam Bean Flour for Instant Noodle Production - , B. N. Effiong; , N. Maduka; , A. G. Essien (Archives of Current Research International, 2018)
Aim: This study is aimed at evaluating instant noodles produced using a composite mixture of wheat and orange-fleshed sweet potato (OFSP) flour fortified with African yam bean (AYB) flour. Study Design: This was an analytical study done in replicates and sensory evaluation by 20 panelists. Place and Duration of Study: This study was conducted in Food Science and Technology Laboratory, the University of Uyo between June-August, 2017. Methodology: Wheat, OFSP, and AYB flour were prepared and subsequently mixed as composite flour in different ratio. They are (80 W: 10 OFSP: 10 AYB); (70 W: 15 OFSP: 15 AYB); (60 W: 20 OFSP: 20 AYB) and (50 W: 20 OFSP: 30 AYB). The control was 100% wheat flour. A nutritional composition including vitamin A and gluten content of individual flour samples and the composite were determined. Composite flour samples were used for noodle production. Previous analysis except gluten content was repeated on the noodle samples including cooking time, water absorption capacity (WAC) and microbial quality assessment using standard methods while sensory acceptability was based on nine points hedonic scale. Results: Moisture, ash, fat, protein, fibre, carbohydrate and vitamin A content of the noodles produced ranged from (11.53-12.40%), (1.35-2.11%), (1.70-2.19%), (11.67-13.04%), (2.13-3.38%), (67.90-70.90%) and (218.03-288.14%), respectively. Noodles produced using (50 W: 20 OFSP: 30 AYB) had the highest protein, fat, fiber and vitamin A content. The other samples compared favorably with the control. Product acceptability based on sensory score showed that the control (wheat noodle) was most preferred while OFSP and AYB supplemented noodles were above average. Cooking time and WAC of the noodle samples ranged between 7.33-10.33 min. and 135.32-154.87%, respectively. Microbiological analysis revealed that the products were within acceptable limits. Conclusion: Instant noodles produced from the composite flour compared favorably with that produced from 100% wheat flour. Among the noodle samples prepared from composite flour, that which comprise 50 W: 20 OFSP: 30 AYB is recommended for noodle industries in Nigeria.